PREVALENCE OF GO AT TUBERCULOSIS IN BARRANCA, PERU - Vergara M., Gino (2011)
The objective of the present study was to determine the prevalence of goat tubercu-losis in districts of the Barranca province, Lima (Paramonga, Pativilca, Barranca andSupe). The unique intradermal test of tuberculin using bovine purified protein derivative(PPD), based on the delayed hypersensitivity reaction was used. A total of 412 criollogoats, older than two months of age, reared in an extensive system, were tested. Theantigen was inoculated in the caudal fold of the tail and the reaction was observed 72hours later. Two animals were positive, determining a prevalence of 0.48 ± 0.67%. Theresults suggest that tuberculosis is scarcely spread in goats of the Barranca province.